A biased analysis of the Swedish management of Covid-19. Issue 3 (September 2021) - Nilson, Finn
Highlights: Whether the Swedish handling of Covid-19 is evidence-based is questionable. There is no empirical evidence that the Swedish strategy has been successful, rather the evidence points to the fact that implementing the Swedish strategy results in higher fatality rates. WHO have been both positive and negative to the Swedish strategy.